1332. Single Dose Oral Amoxicillin Challenge is a Safe and Effective Strategy to Delabel Penicillin Allergies among Low Risk Hospitalized Children. (31st December 2020) - Searns, Justin B; Stein, Amy; MacBrayne, Christine; Sarin, Tara; Lin, Taylor; Duffey, Hannah; Hicks, Allison; Wickstrom, Kaylee; Bajaj, Lalit; Bauer, Maureen; Carel, Kirstin
Abstract: Background: Over 90% of children with reported penicillin allergy can tolerate penicillin without incident. Developing effective and safe strategies to remove inappropriate penicillin allergies has the potential to improve care; however, guidance on how to identify, test, and delabel patients is limited. Methods: In April 2019, Children's Hospital Colorado (CHCO) implemented a penicillin allergy clinical pathway (CP) alongside a risk assessment tool to stratify patients based on allergic history (Figure 1). Patients at "no increased risk" were educated and delabeled without testing. Low risk patients were offered an oral amoxicillin drug challenge with close observation. A single, non-graded, treatment dose of amoxicillin (45 mg/kg, max dose 1000mg) was used for low risk patients, and no preceding allergic skin testing was performed. Patients with no signs or symptoms of allergic response 60 minutes after amoxicillin administration were delabeled. Children delabeled of penicillin allergies on the CHCO hospital medicine service were compared between the pre-CP (1/1/17-3/31/19) and post-CP (4/1/19-3/31/20) cohorts. Figure 1. Penicillin Allergy Risk Assessment Results: Pre-CP, 683/10624 (6.4%) patients reported a penicillin allergy and 18/683 (2.6%) were delabeled by discharge. Post-CP, 345/6559 (5.3%) patients reported a penicillin allergy and 47/345 (13.6%) were delabeled by discharge ( P -value < 0.0001, Figure 2). Among the 47 post-CP patients, 11 were delabeled by history alone, 19 underwent oral amoxicillin drug challenge per CP, and 17 received a different treatment dose penicillin per treatment team. Only one penicillin-exposed patients had a reaction. This patient developed a delayed, non-progressive rash and had penicillin allergy restored to their chart. No patient required emergency medical intervention, and none were "relabeled" penicillin allergic in the 6 months following discharge. Figure 2. Monthly Rate of Penicillin Allergic Patients Delabeled by Discharge Conclusion: A drug challenge using a single non-graded dose of oral amoxicillin is a safe and effective strategy to delabel low risk children of inappropriate penicillin allergies when implemented alongside a risk assessment tool. Further studies are needed to evaluate the long-term benefits of delabeling inappropriate penicillin allergies and to continue monitoring for adverse events. Disclosures: All Authors : No reported disclosures